Gambaran Asupan Zat Gizi Dan Aktivitas Fisik Mahasiswa Ilmu Keolahragaan - Ninoy Yudhistya Sulistiyono Yudhistya (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
The energy need of a person must be the same as their energy intake, this is researcher’s background to conduct the research. The aim of this research is to see the overview of nutrients intake, physical activities, energy needs, and the kind of nutrients that many consumed by the students of sport science. The method used in this research is descriptive method. With population of sports science students, samples were chosen by using purposive sampling technique with the provisions of sports science students, male, and aged between 18-22 years old. The results showed that average BMI of sports science students are normal. For nutrients intake consumed is not in accordance to rules of proportions, while the average physical activity is moderate intensity, and the result of energy balance is apparently not balanced between the energy needs and intake. The conclusion of these results is the nutrients intake consumed by sports science students is not in accordance to the rules of proportions by consuming more fat and less carbohydrate and protein. The type of physical activities that had been done a lot belongs in moderate activity. The type of nutrients that many consumed is carbohydrate nutrients. The balance between energy intake and needs of sports science students is not balanced. If the body mass index is normal then it is not necessarily the energy balance is also balanced. Keywords: Nutrients, Physical Activity, BMI (Body Mass Index).